PENINGKATAN EKSPRESI INTERLEUKIN (IL)-4 BERHUBUNGAN DENGAN PENURUNAN BAX DAN APOPTOSIS LIMFOSIT PADA BRONKIOLUS DAN PARU MENCIT ASMA - Yuliarto, Saptadi; Kusuma, HMS Chandra; Widjajanto, Edi (Jurnal Kedokteran Brawijaya, 2009)
Decrease of lymphocyte  apoptosis is  one factor  that  leads  to  chronic airway inflammation  in  allergic asthma. Previous  studies  revealed  the  role  of  interleukin  (IL)-4  in  preventing  lymphocyte  apoptosis;  however  there  are few  studies  about  the  role  of  lymphocyte-Bax  and  its  relationship  with  IL-4  in  asthma.  The  aim  of  the  study  is  to demonstrate IL-4 role in preventing lymphocyte apoptosis via lymphocyte-Bax inactivation in bronchioli and lungs  of  asthmatic  mice.  It  is  a  randomized  control  group  experimental  study .  The  subject  was  Balb/c  mice  that categorized  into  2  groups:  asthma  and  non-asthma.  Asthma  group  was  sensitized  by  ovalbumin intraperitoneally  in  day  0  and  14,  followed  by  inhalation  every  2-3  days  for  6  weeks.  In  week  8,  all  of  mice were terminated.  The  IL-4  and  lymphocyte-Bax  expression  was  examined  through  immunohistochemistry  method, whereas  lymphocyte  apoptosis  by  TUNEL  method.  Independent  sample  t-test,  Mann  Whitney  U  test, regression  analysis,  and  path  analysis  was  used  in  statistical  analysis  with  confident  interval  95%.  The bronchioli and lungs specimens were obtained from 18 mice (9 in each group). Lymphocyte apoptosis was similar between 2 groups (p=0.1 16), additionally lymphocyte-Bax  decreased in  asthmatic group (p=0.003). This  indicated  low  activity  of  lymphocyte  apoptosis  in  asthmatic  group.